Freedom of Expression in The Movie Spotlight as a Medium to Convey the Voices of Sexual Abuse Victims to the Public - Gunawan, Elisabeth Carolina (VCD, 2021)
Spotlight (2015, directed by Tom McCarthy) is a docudrama which told the story of the investigation of sexual assault of young boys in Catholic Church in Boston, United States of America. A group of four journalists from The Boston Globe, called Spotlight, specialized in investigation overlooked, forgotten cases, and one of the cases is the sexual assault cases that happened inside the Catholic Church. Although their journey to seek the truth has many challenges and problems, they helped a lot of abuse victims to have courage and speak up over the tragedy that happened to them. Spotlight's realistic expression on the narration was shown through the character's dialog, which contributed to the plot of the movie itself. The meaning of "Freedom of Expression" depicted in the movie Spotlight was to symbolize the struggle of the characters, which includes the journalists and the victims, to fight for their rights. Through this movie, McCarthy wanted to help more people who were victims to speak up about their traumatic abuse. Spotlight not only could be a technique of mental healing for victims, but also a media of advocacy for people to know, to inform and to communicate the negative aspects of victim blaming. Keywords: Freedom of expression, docudrama, sexual abuse, victim blaming, advocacy